KOMIKA Media (Children's Comics) Improves Learning Outcomes in Indonesian Cultural Wealth Material for Fourth Grade Elementary School - Nisa Khoirotul Mahfudoh; Ali Sunarso (Journal of Education Reseach and Evaluation, 2024)
The learning activities carried out by teachers use the rote method, so many students need to be more interested and help learn them. Apart from that, the lack of learning media also has a low impact on science learning outcomes for elementary school students. Based on this, this research aims to analyze the influence of KOMIKA (Children's Comics) media on the learning outcomes of Class IV science material and the richness of Indonesian culture in elementary schools. This type of research is quantitative research. The method used in this research is an experimental method with a quasi-experimental design. The population of this study was 32 fourth-grade elementary school students. The method used to collect data is a test. The instrument used to collect data is a test question sheet. The technique used to analyze research results is inferential statistics. The research results, namely the t-test results, show an average difference between the experimental class post-test scores and the control class test scores. The results of the N-gain test show that the N-gain score for the experimental class falls into the high criteria, and for the experimental class falls into the medium criteria. It was concluded that learning using KOMIKA (Children's Comics) media was more effective than using only student books.